Photography in libraries: beyond the technical processes and the promotion of services - Guadamuz Villalobos, Jairo (2019)
The article addresses the importance of the image in the cognition of the human being and through this reflection identifies photography as a resource that can be used with great potential not only in the collection of the library, but also in the digitalization of documents, the promotion of services, cultural management, information literacy, reading animation and the preservation of information. In this last subject a proposal is approached on the utilities that can have in libraries the use of one of the recent photographic techniques: the spherical photography 360. In addition, to carry out these applications of the photography the document proposes a series of characteristics ideal for the profile of the professional in librarianship.